Human Aldo-Keto Reductases 1B1 and 1B10: A Comparative Study on their Enzyme Activity toward Electrophilic Carbonyl Compounds - Shen, Yi (2011)
Aldo-keto reductase family 1 member B1 (AKR1B1, 1B1 in brief) and aldo-keto reductase family 1 member B10 (AKR1B10, 1B10 in brief) are two proteins with high similarities in their amino acid sequences, stereo structures, and substrate specificity. However, these two proteins exhibit distinct tissue distributions; 1B10 is primarily expressed in the gastrointestinal tract and adrenal gland, whereas 1B1 is ubiquitously present in all tissues/organs, suggesting their difference in biological functions. This study evaluated in parallel the enzyme activity of 1B1 and 1B10 toward alpha, beta-unsaturated carbonyl compounds with cellular and dietary origins, including acrolein, crotonaldehyde, 4-hydroxynonenal, trans-2-hexenal, and trans-2,4-hexadienal. Our results showed that 1B10 had much better enzyme activity and turnover rates toward these chemicals than 1B1. By detecting the enzymatic products using high-performance liquid chromatography, we measured their activity to carbonyl compounds at low concentrations. Our data showed that 1B10 efficiently reduced the tested carbonyl compounds at physiological levels, but 1B1 was less effective. Ectopically expressed 1B10 in 293T cells effectively eliminated 4-hydroxynonenal at 5 µM by reducing to 1, 4-dihydroxynonene, whereas endogenously expressed 1B1 did not. The 1B1 and 1B10 both showed enzyme activity to glutathione-conjugated carbonyl compounds, but 1B1 appeared more active in general. Together our data suggests that 1B10 is more effectual in eliminating free electrophilic carbonyl compounds, but 1B1 seems more important in the further detoxification of glutathione-conjugated carbonyl compounds.